FORMATION OF “SPECIAL RELATIONSHIP” BETWEEN REPUBLIC OF BELARUS AND THE RUSSIAN FEDERATION IN THE MIDDLE OF 90TH - Польовий, Т. Є. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The work highlights formation and flow of Belarusian-Russian relations. Analyzed main trends and factors that influenced the bilateral relations. The contents of the main international agreements between Belarus and Russia in the mid-90 - x. years.